Inhibition of ankyrin-B expression reduces growth and invasion of human pancreatic ductal adenocarcinoma - Chen, Ying; Löhr, J.-Matthias; Jesenofsky, Ralf (Pancreatology, 2010)
BACKGROUND: In spite of the increasing knowledge of the molecular pathology of pancreatic ductal adenocarcinoma (PDAC), treatment of this tumor still remains an unresolved problem. Thus, the identification of 'novel' genes involved in pancreatic tumor progression is essential for early diagnosis and new treatment regimens of PDAC. Ankyrin-B (ANK2) was identified as being overexpressed in PDAC in a previous study by our group. ANK2 overexpression has been described in several tumors; however, the function of ANK2 in pancreatic carcinoma has not been elucidated. - MATERIALS AND METHODS: In the present study, we confirmed ANK2 overexpression in PDAC and analyzed the effects of ANK2 knockdown in the pancreatic tumor cell line PANC-1. - RESULTS: ANK2 silencing reduced the activity of FAK, ERK1/2 and p38. Decreased ANK2 expression restrained migration and invasive potential of PANC-1 cells. Moreover, silencing of ANK2 decreased the proliferation of the pancreatic tumor cells and reduced their tumorigenicity in vitro and in vivo. - CONCLUSION: Our results demonstrate that silencing of ANK2 expression reduced the malignant phenotype of pancreatic cancer cells, indicating that ANK2 represents a potential target for therapy of pancreatic cancer.
Gesehen am 03.03.2023